On asymptotic expansions of the characteristic functions of the sum of independent random values - Statulevičius, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Статулявичюс. Об асимптотическом разложении характеристической функции суммы независимых случайных величин V. Statulevičius. Apie nepriklausomų atsitiktinių dydžių sumos charakteringosios funkcijos asimptotinį išdėstymą